Resistance to PD-1/PD-L1 blockade cancer immunotherapy: mechanisms, predictive factors, and future perspectives - Jin-Yu Sun; Dengke Zhang; Songquan Wu; Min Xu; Xiao Zhou; Xiao-Jie Lu; Jiansong Ji (BMC, 2020)
Abstract PD-1/PD-L1 blockade therapy is a promising cancer treatment strategy, which has revolutionized the treatment landscape of malignancies. Over the last decade, PD-1/PD-L1 blockade therapy has been trialed in a broad range of malignancies and achieved clinical success. Despite the potentially cure-like survival benefit, only a minority of patients are estimated to experience a positive response to PD-1/PD-L1 blockade therapy, and the primary or acquired resistance might eventually lead to cancer progression in patients with clinical responses. Accordingly, the resistance to PD-1/PD-L1 blockade remains a significant challenge hindering its further application. To overcome the limitation in therapy resistance, substantial effort has been made to improve or develop novel anti-PD-1/PD-L1 based immunotherapy strategies with better clinical response and reduced immune-mediated toxicity. In this review, we provide an overview on the resistance to PD-1/PD-L1 blockade and briefly introduce the mechanisms underlying therapy resistance. Moreover, we summarize potential predictive factors for the resistance to PD-1/PD-L1 blockade. Furthermore, we give an insight into the possible solutions to improve efficacy and clinical response. In the following research, combined efforts of basic researchers and clinicians are required to address the limitation of therapy resistance.